Anti-Icing Engine Damage Analysis Boeing 737 - 800 Ng With Fault Tree Analysis Method - Arif Pambekti; Indro Lukito; Cyrilus Sukaca Budiono; Riski Kurniawan (Journal of Business, Social and Technology, 2022)
An Anti-icing system is a system that aims to prevent the formation of ice when the plane is in the air. The formation of ice in aircraft is of great concern because an airplane flight will pass through the atmosphere, which will experience the formation of the ice at a certain altitude. The formation of such ice will cause a hazard to the aircraft. So that the ice protection system, namely the anti-icing system, is very concerned so that it is always in a serviceable condition. In this study, direct observation and fault tree analysis were used to determine the cause of failure of the Boeing 737-800 NG anti-ice system engine and anti-icing cowl inlet. The results of the analysis using the fault tree analysis method obtained essential events, namely: actuator fails, electrical connector disconnected, Control Selenoid Trouble, Regulator Trouble, Sense Line Connector Trouble, Engine Fault, Engine Control Trouble, Engine Duct Trouble, Panel Buttom Problem, EICAS Module Problem, No Source Electricity, Negative Electrical Source, Wiring Problem.